2016
DOI: 10.15296/ijwhr.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Bladder Flap Hematoma Presenting With Hematuria

Abstract: IntroductionBladder flap hematoma is an unusual complication of cesarean delivery. The exact incidence is unknown (1). A few paper has been written on this surgical complication (2-5). Bladder flap formation has been an important step in standard cesarean delivery. A cesarean delivery can be performed either by suturing or not suturing the visceral peritoneum. When visceral peritoneum is reapproximated, bleeding at the incision site may result in bladder flap hematoma. The traditional method closes visceral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 5 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Some studies have evaluated the value of some blood cell count indices, especially NLR and PLR, and reported that these biomarkers may be related to POI (3,13).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have evaluated the value of some blood cell count indices, especially NLR and PLR, and reported that these biomarkers may be related to POI (3,13).…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial to use the most effective and safe surgical technique. Standard and evidence-based techniques are essential to minimize surgical complications [8]. Misgav Ladach was chosen for the cesarean section in this case.…”
Section: Discussionmentioning
confidence: 99%
“…ultrasonography shows a well-circumferenced complex collection between the bladder and uterus, causing posterior shading [17]. During the following hours, the fusion of blood through the bladder is the reason for the hematuria [8]. The scientific literature does not have a clear protocol regarding BFH management or its surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usual presentations include a palpable mass, suprapubic pain, signs of hypovolemia and fever [5]. No standardized protocols exist for management of post CS BFH [6].…”
Section: Introductionmentioning
confidence: 99%